Primates of Park Avenue [compact disc, unabridged] : a memoir - Martin, Wednesday (Simon & Schuster Audio, 2015)
After marrying a man from the Upper East Side and moving to the neighborhood, Wednesday Martin struggled to fit in. Drawing on her background in anthropology and primatology, she tried looking at her new world through that lens, and suddenly things fell into place. She understood the other mothers₂ snobbiness at school drop-off when she compared them to olive baboons. Her obsessional quest for a Hermes Birkin handbag made sense when she realized other females wielded them to establish dominance.